Towards an odour-baited trap to control Musca sorbens, the putative vector of trachoma - Ailie Robinson; Jack Bickford-Smith; Oumer Abdurahman Shafi; Muluadam Abraham Aga; Gemeda Shuka; Dereje Debela; Gebreyes Hordofa; Wondu Alemayehu; Virginia Sarah; Anna Last; David MacLeod; Matthew J. Burton; et al. (Scientific Reports, 2021)
Abstract Musca sorbens is a synanthropic filth fly that aggressively attacks people to feed from mucous membranes of the eyes, nose or mouth, from open sores, or from sweat. It has long been suspected that this fly contributes to the transmission of eye infections, particularly trachoma, and recent work has added to the evidence base that M. sorbens is a trachoma vector in Ethiopia. There are few options to control M. sorbens, largely due to a lack of evidence. Space spraying with insecticides is effective, but an environmentally sound and long-term sustainable solution would be better, for example, mass trapping. We tested commercially available and homemade trap types in a pilot (laboratory) study and three field studies. A homemade design, built from a bucket and two empty water bottles, baited with a commercially available lure, The Buzz, was found to be most effective. This trap caught 3848 M . sorbens over 26 trap ‘events’ (3- or 4-day periods); mean/median per 24 h 43.6 (standard deviation 137.10)/2.25 (IQR 0.25–12.67). The Buzz lure is cheap and effective for 4 weeks, and trap components cheap and locally available. Further studies are needed to understand the impact of this trap on local fly populations and the local transmission of trachoma.